Method for preparing high-early-strength liquid alkali-free accelerator by using by-product fluorosilicon slag and application thereof

CN122464630BActive Publication Date: 2026-10-16SHANXI SUNWAY INTION TRADE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610935937.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-16
Estimated Expiration
2046-06-26

AI Technical Summary

Technical Problem

[0004]然而,现有液体无碱速凝剂尤其是硫酸铝基体系仍面临产品稳定性不足、实际掺量偏高、早期强度发展慢等共性问题,为提升早期强度,研究人员尝试在速凝剂中添加纳米二氧化硅,利用其粒径小、比表面积大以及火山灰效应和微集料填充效应,促进水泥水化产物成核以加速早期强度发展,但纳米二氧化硅价格昂贵,表面改性工艺复杂,限制了其在液体无碱速凝剂中的大规模应用

Benefits of technology

本发明实现了副产氟硅渣的高值化利用,显著降低了原材料成本,以氟硅酸湿法生产氟化铝工艺产生的危险固体废弃物氟硅渣为原料,通过微波辅助定向活化、离子印迹缓释和分级粒径研磨联用工艺制备微纳米硅浆,替代了传统液体无碱速凝剂中价格昂贵的纳米二氧化硅或硅溶胶,在实现工业固废资源化利用的同时,大幅降低了产品生产成本,具有显著的经济效益和环境效益;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122464630B_ABST
    Figure CN122464630B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing high-early-strength liquid alkali-free accelerator by using by-product fluorosilicon slag and application, and particularly relates to the technical field of building materials. The application uses by-product fluorosilicon slag generated in the process of producing aluminum fluoride by fluorosilicic acid wet method as raw material, and prepares micro-nano silicon slurry with bimodal particle size distribution through a combined process of microwave-assisted directional activation, ion imprinting slow release and grading particle size grinding. The micro-nano silicon slurry is mixed with aluminum sulfate, alcohol amine and other components to form liquid alkali-free accelerator through a three-stage gradient reaction process. The prepared accelerator has the advantages of short setting time, high early strength, good late strength retention rate and excellent storage stability, and realizes high-value utilization of industrial hazardous solid waste, and reduces production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and more specifically, to a method and application for preparing a high early strength liquid alkali-free quick-setting agent using by-product fluorosilicone slag. Background Technology

[0002] In tunnel engineering, mine support, water conservancy and hydropower, and waterproofing and leak sealing projects, shotcrete technology has become an indispensable construction method. As a key admixture in shotcrete, quick-setting agent enables concrete to set and harden quickly, which plays an important role in ensuring construction efficiency and project safety.

[0003] As wet spraying gradually replaces traditional dry spraying, liquid accelerators have become the mainstream in the market. Currently, liquid accelerators are mainly divided into two categories: alkali-based accelerators and alkali-free accelerators. Alkali-based accelerators have disadvantages such as high alkali content, easy induction of alkali-aggregate reaction, large strength loss in the later stage, and high rebound rate. In contrast, liquid alkali-free accelerators have advantages such as low alkali content, small rebound, low shrinkage rate of hardened concrete, good strength retention in the later stage, and more friendly to the construction environment, and have been widely studied and applied.

[0004] However, existing liquid alkali-free accelerators, especially aluminum sulfate-based systems, still face common problems such as insufficient product stability, excessively high actual dosage, and slow early strength development. To improve early strength, researchers have tried adding nano-silica to accelerators, utilizing its small particle size, large specific surface area, pozzolanic effect, and micro-aggregate filling effect to promote the nucleation of cement hydration products and accelerate early strength development. However, nano-silica is expensive and its surface modification process is complex, which limits its large-scale application in liquid alkali-free accelerators.

[0005] In recent years, utilizing industrial by-product fluorosilicone slag as a silicon source to replace nano-silica has become a research direction. The wet process for producing aluminum fluoride from fluorosilicic acid generates a large amount of solid waste slag containing fluorine-containing silica, whose main component is hydrated silica, and contains small amounts of aluminum, fluorine, and other components. Some studies have attempted to use fluorosilicone slag to prepare accelerators, but the existing technology still has the following shortcomings: First, improper treatment of fluorine in fluorosilicone slag can cause fluorine to react prematurely with calcium ions to form calcium fluoride precipitate, which hinders the cement hydration process. Second, the activation degree of silicon species in fluorosilicone slag is limited, making it difficult to fully utilize the nanocrystal nucleation effect. Third, the early strength and long-term stability of existing accelerator products still need to be improved.

[0006] Therefore, developing a liquid alkali-free quick-setting agent that can fully utilize the silicon and fluorine components in fluorosilicone slag, and has high early strength, high stability, and low cost, has significant industrial application value. Summary of the Invention

[0007] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present invention provide a method and application for preparing a high early strength liquid alkali-free quick-setting agent using by-product fluorosilicone slag, so as to solve the problems mentioned in the background art.

[0008] To achieve the above objectives, the present invention provides the following technical solution: On the one hand, the present invention provides a method for preparing a high early strength liquid alkali-free quick-setting agent using by-product fluorosilicone slag, comprising the following steps: mixing 40%-60% aluminum sulfate, 5%-20% micro-nano silica slurry, 5%-10% alkanolamine, 0%-10% early strength agent, and 0%-2% acidity regulator with water to make up to 100% by mass percentage to obtain a high early strength liquid alkali-free quick-setting agent; The micro-nano silicon slurry is composed of the following components by mass percentage: 50%-80% by-product fluorosilicone slag, 2%-5% concentrated sulfuric acid, 5%-10% alkanolamine, 1%-5% seed crystal guide, 0.5%-3% fluoride ion complexing agent, 0.5%-2.0% dispersant, 0.5%-2.0% suspending agent, and the balance being water.

[0009] Preferably, the micro / nano silica paste is prepared by a method comprising the following steps: S1. Add water and by-product fluorosilicone slag to the reactor, add seed crystal directing agent, and initially disperse for 5-10 minutes; S2. Add concentrated sulfuric acid, heat to 60℃-80℃, turn on the microwave-assisted device, and react for 30min-60min. S3. Add alcohol amine, adjust the pH of the slurry to 8-10, add fluoride ion complexing agent, maintain the temperature at 60℃-80℃, and react for 15min-30min. S4. Add dispersant and suspending agent, and disperse for 15-60 minutes using a high-speed shear disperser at a speed of 1000-5000 rpm. S5. The obtained slurry is filtered through a 1μm-10μm vibrating screen and transferred to a classifying ball mill for gradient grinding to obtain a micro-nano silica slurry with a bimodal particle size distribution, wherein the first particle size peak D501 is 200nm-500nm and the second particle size peak D502 is 1μm-5μm. The gradient grinding process includes, in sequence: Grind at 100rpm-200rpm for 30min-60min; Grind at 300rpm-500rpm for 60min-90min; Grind at 600rpm-800rpm for 30min-60min.

[0010] Preferably, the by-product fluorosilicone slag is a solid waste generated from the wet process of producing aluminum fluoride from fluorosilicic acid, and its components include hydrated silica, aluminum fluoride trihydrate, aluminum hydroxide and hexafluorosilicic acid, with a weight loss of 40%-50% upon heating.

[0011] Preferably, the seed crystal directing agent is selected from one or more of nano-calcite seed crystal suspension, nano-hydrated calcium silicate crystal nucleus suspension, and nano-hydrated calcium aluminosilicate crystal nucleus suspension, with an average particle size of 20nm-100nm and a solid content of 10%-30%. The fluoride ion complexing agent is selected from one or more of triethanolamine borate, diethanolamine borate, carboxymethyl-β-cyclodextrin, and hydroxypropyl-β-cyclodextrin.

[0012] Preferably, the concentrated sulfuric acid in the micro / nano silica slurry has a mass fraction of ≥98%; The alkanolamine in the micro-nano silica paste is one or both of diethanolamine and triethanolamine; The dispersant is an anionic or nonionic polymer; The suspending agent is one or more of bentonite, hydrated magnesium silicate, carboxymethyl cellulose, hydroxypropyl methyl cellulose, and polyacrylamide.

[0013] Preferably, the alkanolamine in the quick-setting agent is one or more of diethanolamine, triethanolamine, and triisopropanolamine; The early strength agent is one or more of magnesium sulfate, hydrated magnesium sulfate, lithium sulfate, hydrated lithium sulfate, and calcium formate. The acidity regulator is one or more of phosphoric acid, formic acid, acetic acid, and lactic acid.

[0014] Preferably, the mixing step specifically includes: First stage: Add water and micro / nano silica slurry to the reactor, heat to 80℃-95℃, adjust pH to 3.0-4.0, add the first part of aluminum sulfate, which accounts for 30%-50% of the total aluminum sulfate, stir and react for 60min-120min to obtain a mixture containing aluminosilicate layered precursors; Second stage: Cool the reaction system to 50℃-65℃, add alcohol amine, stir the reaction for 60min-120min, and obtain a mixture with stable alcohol amine complexation. The third stage: Cool the reaction system to 40℃-50℃, adjust the pH to 7.5-8.5, add the second part of aluminum sulfate, early strength agent, acidity regulator and nano crystal seed suspension, stir and react for 30min-60min to obtain a high early strength liquid alkali-free quick-setting agent. The second part of aluminum sulfate accounts for 50%-70% of the total aluminum sulfate, and the amount of nano crystal seed suspension added is 0.5%-2.0% of the total mass of the quick-setting agent.

[0015] Preferably, the nanocrystal seed suspension is a nano-hydrated calcium silicate crystal nucleus suspension or a nano-hydrated calcium aluminosilicate crystal nucleus suspension.

[0016] Preferably, the pH value of the high early strength liquid alkali-free quick-setting agent is 2.5-4.5.

[0017] On the other hand, the present invention also provides the application of the above-mentioned high early strength liquid alkali-free quick-setting agent in shotcrete, wherein the dosage of the quick-setting agent is 6%-9% of the cement dosage.

[0018] The technical effects and advantages of this invention are as follows: This invention realizes the high-value utilization of by-product fluorosilicone slag, significantly reducing raw material costs. Using fluorosilicone slag, a hazardous solid waste generated from the wet process of producing aluminum fluoride from fluorosilicic acid, as raw material, micro-nano silica slurry is prepared through a combination of microwave-assisted directional activation, ion-imprinted slow release, and graded particle size grinding. This slurry replaces the expensive nano-silica or silica sol in traditional liquid alkali-free quick-setting agents. While realizing the resource utilization of industrial solid waste, it significantly reduces product production costs, resulting in significant economic and environmental benefits. The liquid alkali-free quick-setting agent prepared by this invention has excellent early strength performance and high stability. By introducing a seed crystal guide and a fluoride ion complexing agent, the directional activation of silicon species and the selective slow release of fluoride ions are achieved, avoiding the hindrance of hydration by premature precipitation of calcium fluoride. At the same time, the micro-nano silicon slurry with a bimodal particle size distribution is obtained by graded grinding. The fine particles exert the crystal nucleation effect, and the coarse particles exert the micro-aggregate filling effect, which synergistically accelerates cement hydration. The resulting quick-setting agent has a significantly shortened setting time, a greatly improved early strength, good storage stability, and its comprehensive performance is significantly better than that of the prior art. The accelerator prepared by this invention has a high late-stage strength retention rate and no adverse effect on concrete durability. It adopts a three-stage gradient reaction process to form a multi-level composite structure of aluminosilicate precursor-alkanolamine complex-nanocrystalline seed inside the accelerator. While accelerating early hydration, it does not impair the later-stage strength development. The late-stage compressive strength retention rate is significantly better than that of similar products on the market, ensuring the long-term safe service of shotcrete projects. Attached Figure Description

[0019] Figure 1 This is a process flow diagram for preparing the high early strength liquid alkali-free quick-setting agent of the present invention.

[0020] Figure 2 This is a flowchart of the micro / nano silicon slurry preparation process of the present invention. Detailed Implementation

[0021] To make the present invention easier to understand, the present invention will be described in detail below with reference to embodiments. These embodiments are for illustrative purposes only and are not limited to the scope of application of the present invention. Unless otherwise specified, the raw materials used in the embodiments and comparative examples are all commercially available industrial-grade products.

[0022] The source of raw materials is explained as follows: By-product fluorosilicone slag: Produced by the wet process of producing aluminum fluoride from fluorosilicic acid, it is a white, damp powder with a pungent odor. Its main components are hydrated silica and small amounts of aluminum fluoride trihydrate, aluminum hydroxide, and hexafluorosilicic acid. Testing of multiple batches of this by-product fluorosilicone slag showed that its weight loss upon heating is typically between 40% and 50%, with an average of approximately 45.2% (weight loss upon heating was determined according to GB / T 6284-2006 "General Method for Determination of Moisture in Chemical Products - Loss on Drying Method", dried at 105℃ to constant weight). Industrial aluminum sulfate: It appears as a white, flaky solid with an aluminum oxide mass fraction of 15.6%.

[0023] Dispersant: BYK Chemicals DISPERBYK-190 anionic polymer with a number average molecular weight of approximately 20 kDa was selected; Concentrated sulfuric acid: 98.3% by mass; Suspension agent: Torza hydrated magnesium silicate PANGEL S9; Seed guiding agent: Nano-hydrated calcium silicate crystal nucleus suspension (used for the preparation of micro-nano silica slurry), with an average particle size of 50 nm and a solid content of 20%; Fluoride ion complexing agent: triethanolamine borate; Nanocrystalline seed suspension: A nano-hydrated calcium silicate crystal nucleus suspension used in the third stage of quick-setting agent addition, with an average particle size of 20nm and a solid content of 15%; Alkylamines, early strength agents, acidity regulators, etc. are all commercially available general products.

[0024] The general preparation method of micro / nano silica paste is as follows: Unless otherwise specified, the micro / nano silica pastes used in the following examples and comparative examples were all prepared by the following methods: S1. Add water and by-product fluorosilicone slag to the reactor, add seed crystal directing agent, and initially disperse for 5-10 minutes; S2. Add concentrated sulfuric acid, heat to 60℃-80℃, turn on the microwave-assisted device, and react for 30min-60min. S3. Add alcohol amine, adjust the pH of the slurry to 8-10, add fluoride ion complexing agent, maintain the temperature at 60℃-80℃, and react for 15min-30min. S4. Add dispersant and suspending agent, and disperse for 15-60 minutes using a high-speed shear disperser at a speed of 1000-5000 rpm. S5. The obtained slurry is filtered through a 1μm-10μm vibrating screen and transferred to a classifying ball mill for gradient grinding to obtain a micro-nano silica slurry with a bimodal particle size distribution, wherein the first particle size peak D501 is 200nm-500nm and the second particle size peak D502 is 1μm-5μm. Gradient grinding consists of grinding at 100 rpm to 200 rpm for 30 min to 60 min. Grind at 300rpm-500rpm for 60min-90min; Grind at 600rpm-800rpm for 30min-60min.

[0025] Specifically, in this preparation method: A calculated amount of water, 65 wt% of by-product fluorosilicone slag, and 3 wt% of nano-hydrated calcium silicate crystal nuclei suspension are added to the reactor and dispersed by stirring at 500 rpm for 10 min. 2.5 wt% concentrated sulfuric acid is added, and the microwave-assisted device is turned on at a frequency of 2.45 GHz and a power density of 1.0 W / g. The temperature is raised to 70℃, and the reaction is carried out for 45 min. 7.5 wt% triethanolamine is added to adjust the pH of the slurry to 9.0, and 1.5 wt% triethanolamine borate is added. The reaction is maintained at 70℃ for 20 min. 1.0 wt% dispersant and 1.5 wt% suspending agent are added, and the stirring speed is increased to 3000 rpm for high-speed shear dispersion for 30 min. The slurry was filtered through a 5μm vibrating screen, and then transferred to a classifying ball mill. It was ground at 150 rpm for 45 minutes using Φ10mm zirconia balls as the grinding media; then at 400 rpm for 75 minutes using Φ4mm zirconia balls; and finally at 700 rpm for 45 minutes using Φ0.8mm zirconia balls, yielding micro / nano silica slurry. Laser particle size analysis showed a bimodal particle size distribution: D501≈320nm, D502≈2.8μm, with a solid content of approximately 45%.

[0026] A general three-stage gradient reaction process for high early-strength liquid alkali-free quick-setting agents: First stage: Add water and micro / nano silica slurry to the reactor, heat to 80℃-95℃, adjust pH to 3.0-4.0, add the first part of aluminum sulfate, which accounts for 30%-50% of the total aluminum sulfate, stir and react for 60min-120min to obtain a mixture containing aluminosilicate layered precursors; Second stage: Cool the reaction system to 50℃-65℃, add alcohol amine, stir the reaction for 60min-120min, and obtain a mixture with stable alcohol amine complexation. The third stage: Cool the reaction system to 40℃-50℃, adjust the pH to 7.5-8.5, add the second part of aluminum sulfate, early strength agent, acidity regulator and nano crystal seed suspension, stir and react for 30min-60min to obtain a high early strength liquid alkali-free quick-setting agent. The second part of aluminum sulfate accounts for 50%-70% of the total aluminum sulfate, and the amount of nano crystal seed suspension added is 0.5%-2.0% of the total mass of the quick-setting agent. Example 1

[0027] In this embodiment, the components are aluminum sulfate 55%, micro-nano silica paste 8%, diethanolamine 8%, magnesium sulfate 5%, phosphoric acid 1%, and water to make up to 100% by mass percentage.

[0028] The accelerator was prepared using the aforementioned micro / nano silica slurry and a general three-stage gradient reaction process. The specific steps are as follows: S1. Add water and 8% micro-nano silica slurry to the reactor, heat to 90℃, adjust the pH to 3.5 with phosphoric acid, add the first part of aluminum sulfate, the first part of aluminum sulfate accounts for 40% of the total aluminum sulfate, stir and react for 90 min to obtain a mixture containing aluminum silicate layered precursor. S2. Cool the reaction system to 60°C, add 8% diethanolamine, stir the reaction for 90 min, and obtain a mixture with stable alcohol amine complexation. S3. Cool the reaction system to 45°C, adjust the pH to 8.0 with phosphoric acid, add the second portion of aluminum sulfate (60% of the total aluminum sulfate), then add 5% magnesium sulfate and 1.0% nanocrystalline seed suspension, stir and react for 45 minutes, cool to room temperature, and discharge to obtain the quick-setting agent of Example 1. The pH value of this quick-setting agent was tested to be 3.0. Example 2

[0029] The only difference between Example 2 and Example 1 is the formulation composition; the other preparation steps and conditions are the same.

[0030] The formulation for Example 2 is as follows: 50% aluminum sulfate, 15% micro / nano silica paste, 8% diethanolamine, 5% magnesium sulfate, 1% phosphoric acid, and water to make up to 100%. In the three-stage reaction: the first part of aluminum sulfate accounts for 40% of the total aluminum sulfate, and the second part of aluminum sulfate accounts for 60% of the total aluminum sulfate.

[0031] Everything else is the same as in Example 1.

[0032] The pH value of the quick-setting agent was tested to be 3.2. Example 3

[0033] The only difference between Example 3 and Example 1 is the formulation composition; the other preparation steps and conditions are the same.

[0034] The formulation of Example 3 is as follows: 45% aluminum sulfate, 20% micro / nano silica paste, 8% diethanolamine, 5% magnesium sulfate, 1% phosphoric acid, and water to make up to 100%. In the three-stage reaction: the first part of aluminum sulfate accounts for 40% of the total aluminum sulfate, and the second part of aluminum sulfate accounts for 60% of the total aluminum sulfate.

[0035] Everything else is the same as in Example 1.

[0036] The pH value of the quick-setting agent was tested to be 3.1. Example 4

[0037] The difference between Example 4 and Example 1 is that no early strength agent is added to the formula, while the rest of the preparation steps and conditions are the same.

[0038] The formulation for Example 4 is as follows: 50% aluminum sulfate, 15% micro / nano silica paste, 8% diethanolamine, 0% magnesium sulfate, 1% phosphoric acid, and water to make up to 100%. In the three-stage reaction: the first part is aluminum sulfate, which accounts for 40% of the total aluminum sulfate; the second part is aluminum sulfate, which accounts for 60% of the total aluminum sulfate; and no magnesium sulfate is added in the third stage.

[0039] Everything else is the same as in Example 1.

[0040] The pH value of the quick-setting agent was tested to be 3.3. Example 5

[0041] The difference between Example 5 and Example 1 is that no acidity regulator is added to the formula, while the rest of the preparation steps and conditions are the same.

[0042] The formulation of Example 5 is as follows: 50% aluminum sulfate, 15% micro / nano silica paste, 8% diethanolamine, 5% magnesium sulfate, 0% phosphoric acid, and water to make up to 100%. In the three-stage reaction: in the first stage, no phosphoric acid is added to adjust the pH, and the pH of the system is approximately 4.5. In the third stage, no phosphoric acid is added to adjust the pH.

[0043] Everything else is the same as in Example 1.

[0044] The pH value of the quick-setting agent was tested to be 4.2.

[0045] Comparative Example 1 Comparative Example 1 is a control example without micro / nano silica paste. Except for not adding micro / nano silica paste and replacing it with water by the same mass, the rest of the formulation is the same as in Example 2.

[0046] That is: 50% aluminum sulfate, 8% diethanolamine, 5% magnesium sulfate, 1% phosphoric acid, and water to make up to 100%; The same three-stage gradient reaction process as in Example 2 was used to prepare the quick-setting agent, but instead of adding micro-nano silica slurry in the first stage, water was used directly to obtain Comparative Example 1.

[0047] Comparative Example 2 Comparative Example 2 uses unactivated raw fluorosilicone slag instead of micro-nano silicon slurry. Raw fluorosilicone slag with equal solid content that has not been treated by microwave-assisted directional activation, ion imprinting slow release and graded grinding processes is used instead of the micro-nano silicon slurry in Example 2. The raw fluorosilicone slag is taken directly from the factory without any treatment and is added in dry powder form after being converted according to the solid content. The other components are the same as in Example 2.

[0048] The same three-stage gradient reaction process as in Example 2 was used to prepare the accelerator for Comparative Example 2.

[0049] Comparative Example 3 Comparative Example 3 uses purchased nano-silica instead of micro-nano silica slurry. Purchased nano-silica slurry with equal solid content is used instead of micro-nano silica slurry in Example 2. The nano-silica slurry has an average particle size of 50 nm and a solid content of 40%.

[0050] The remaining components are the same as in Example 2.

[0051] The same three-stage gradient reaction process as in Example 2 was used to prepare the accelerator for Comparative Example 3.

[0052] Comparative Example 4 Comparative Example 4 is a commercially available conventional product. A mainstream commercially available liquid alkali-free quick-setting agent was selected as a reference. The main components of this product are aluminum sulfate and alkanolamine, and it does not contain nano-reinforcing phase. It was purchased and used directly without further preparation.

[0053] Comparative Example 5 Comparative Example 5 was prepared using a single-particle-size micro / nano silica slurry and a one-step mixing method.

[0054] The micro-nano silicon slurry was prepared using a conventional ball milling process: without distinguishing between gradient milling, it was milled at 400 rpm for 120 min to obtain a single-particle-size micro-nano silicon slurry with a D50≈350nm, and no seed crystal guiding agent or fluoride ion complexing agent was added during the preparation process.

[0055] The quick-setting agent formulation is the same as in Example 2, but the preparation adopts a one-step mixing method: all components, namely 50% aluminum sulfate, 15% of the above single-particle-size micro-nano silica slurry, 8% diethanolamine, 5% magnesium sulfate, and 1% phosphoric acid, are added to the reactor at the same time, stirred at 50°C for 120 min, cooled and discharged to obtain the quick-setting agent of Comparative Example 5.

[0056] Below, the liquid alkali-free quick-setting agent products obtained in Examples 1-5 and Comparative Examples 1-5 were subjected to performance tests in accordance with GB / T 35159-2017 "Quick-setting Agents for Shotcrete" standard, with a dosage of 8% of the cement weight. The test results are shown in the table below:

[0057] As can be seen from the data in the table above, the initial setting time of Examples 1-5 of the present invention is 1 min 05 s-1 min 25 s, and the final setting time is 3 min 15 s-3 min 55 s, which is significantly better than the comparative examples. The compressive strength at 1 day reaches 17.5 MPa-20.1 MPa, the compressive strength at 6 hours reaches 2.9 MPa-3.9 MPa, the compressive strength retention rate at 90 days reaches 118%-122%, and the precipitation amount during 6 months of storage stability is only 0.5 mL-2 mL. Among them, Example 2 has the best overall performance and is the best implementation method of the present invention. Comparative Example 1, without the addition of micro / nano silica slurry, had the slowest setting time and the lowest strength. Comparative Example 2, using unactivated raw fluorosilicone slag, showed a significant decrease in performance. Comparative Example 3, using purchased nano silica, exhibited lower stability and earlier strength compared to the embodiments of the present invention. Comparative Example 4 had a precipitation volume of 1 mL, comparable to Example 1, but Examples 2 and 4 showed better stability (precipitation volume of 0.5 mL). It should be noted that the precipitation volumes of Examples 3 and 5 were 1.5 mL and 2 mL, respectively, slightly higher than Comparative Example 4. However, the precipitates of all examples were loose precipitates, which could be completely restored to a homogeneous state with slight stirring, and all met the requirements of GB / T35159-2017 for storage stability (no hardening, used after uniform stirring). The actual performance was not affected. Comparative Example 5, prepared using single-particle-size micro / nano silica slurry and a one-step mixing method, showed significantly inferior performance compared to the embodiments of the present invention, demonstrating that the combined technical scheme of microwave-assisted activation, ion complexation, graded grinding, and three-stage gradient reaction in the present invention produced a synergistic effect.

[0058] The high early strength liquid alkali-free quick-setting agent prepared by this invention can be directly applied to shotcrete projects. When using it, it should be added at 6% to 9% of the cement mass. The product can be stored at room temperature for more than 6 months. It can be restored to a uniform state by slight stirring before use.

[0059] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a high early-strength liquid alkali-free accelerator using by-product fluorosilicone slag, characterized in that: Includes the following steps: Based on the mass percentage, 40%-60% aluminum sulfate, 5%-20% micro-nano silica slurry, 5%-10% alkanolamine, 0%-10% early strength agent, 0%-2% acidity regulator, and 0.5%-2.0% nano crystal seed suspension are mixed with water to make up to 100% to prepare a high early strength liquid alkali-free quick-setting agent. The micro-nano silicon slurry is composed of the following components in mass percentage: 50%-80% by-product fluorosilicone slag, 2%-5% concentrated sulfuric acid, 5%-10% alkanolamine, 1%-5% seed crystal guide, 0.5%-3% fluoride ion complexing agent, 0.5%-2.0% dispersant, 0.5%-2.0% suspending agent, and the balance being water; The micro / nano silica paste is prepared by a method comprising the following steps: S1. Add water and by-product fluorosilicone slag to the reactor, add seed crystal directing agent, and initially disperse for 5-10 minutes; S2. Add concentrated sulfuric acid, heat to 60℃-80℃, turn on the microwave-assisted device, and react for 30min-60min. S3. Add alcohol amine, adjust the pH of the slurry to 8-10, add fluoride ion complexing agent, maintain the temperature at 60℃-80℃, and react for 15min-30min. S4. Add dispersant and suspending agent, and disperse for 15-60 minutes using a high-speed shear disperser at a speed of 1000-5000 rpm. S5. The obtained slurry is filtered through a 1μm-10μm vibrating screen and transferred to a classifying ball mill for gradient grinding to obtain a micro-nano silica slurry with a bimodal particle size distribution, wherein the first particle size peak D501 is 200nm-500nm and the second particle size peak D502 is 1μm-5μm. The gradient grinding process includes, in sequence: Grind at 100rpm-200rpm for 30min-60min; Grind at 300rpm-500rpm for 60min-90min; Grind at 600rpm-800rpm for 30min-60min.

2. The method according to claim 1, characterized in that: The by-product fluorosilicone slag is a solid waste generated from the wet process of producing aluminum fluoride from fluorosilicic acid. Its components include hydrated silica, aluminum fluoride trihydrate, aluminum hydroxide and hexafluorosilicic acid, and its weight loss upon heating is 40%-50%.

3. The method according to claim 1, characterized in that: The seed crystal directing agent is selected from one or more of the following: nano-calcite seed crystal suspension, nano-hydrated calcium silicate crystal nucleus suspension, and nano-hydrated calcium aluminosilicate crystal nucleus suspension, with an average particle size of 20nm-100nm and a solid content of 10%-30%. The fluoride ion complexing agent is selected from one or more of triethanolamine borate, diethanolamine borate, carboxymethyl-β-cyclodextrin, and hydroxypropyl-β-cyclodextrin.

4. The method according to claim 1, characterized in that: The concentrated sulfuric acid mass fraction in the micro-nano silica slurry is ≥98%; The alkanolamine in the micro-nano silica paste is one or both of diethanolamine and triethanolamine; The dispersant is an anionic or nonionic polymer; The suspending agent is one or more of bentonite, hydrated magnesium silicate, carboxymethyl cellulose, hydroxypropyl methyl cellulose, and polyacrylamide.

5. The method according to claim 1, characterized in that: The amine in the quick-setting agent is one or more of diethanolamine, triethanolamine, and triisopropanolamine; The early strength agent is one or more of magnesium sulfate, hydrated magnesium sulfate, lithium sulfate, hydrated lithium sulfate, and calcium formate. The acidity regulator is one or more of phosphoric acid, formic acid, acetic acid, and lactic acid.

6. The method according to claim 1, characterized in that: The mixing steps specifically include: First stage: Add water and micro / nano silica slurry to the reactor, heat to 80℃-95℃, adjust pH to 3.0-4.0, add the first part of aluminum sulfate, which accounts for 30%-50% of the total aluminum sulfate, stir and react for 60min-120min to obtain a mixture containing aluminosilicate layered precursors; Second stage: Cool the reaction system to 50℃-65℃, add alcohol amine, stir the reaction for 60min-120min, and obtain a mixture with stable alcohol amine complexation. The third stage: Cool the reaction system to 40℃-50℃, adjust the pH to 7.5-8.5, add the second part of aluminum sulfate, early strength agent, acidity regulator and nano crystal seed suspension, stir the reaction for 30min-60min to obtain a high early strength liquid alkali-free quick-setting agent, the second part of aluminum sulfate accounts for 50%-70% of the total aluminum sulfate.

7. The method according to claim 6, characterized in that: The nanocrystal seed suspension is a nano-hydrated calcium silicate crystal nucleus suspension or a nano-hydrated calcium aluminosilicate crystal nucleus suspension.

8. The method according to claim 1, characterized in that: The pH value of the high early strength liquid alkali-free quick-setting agent is 2.5-4.

5.

9. The application of a high early-strength liquid alkali-free quick-setting agent prepared by the method according to any one of claims 1-8 in shotcrete, characterized in that: The dosage of the quick-setting agent is 6%-9% of the cement dosage.

Citation Information

Patent Citations

  • Environment-friendly early-strength alkali-free accelerator as well as preparation method and application thereof

    CN121248181A

  • Defluorination activation and resource recycling method for fluorine-containing silicon slag

    CN122166823A